Archaeology with art - Chittock, Helen,; Valdez-Tullett, Joana, (Archaeopress archaeology., 2016)
The result of a 2013 Theoretical Archaeology Group (TAG) conference session, this work aims to merge the perspectives of artists and archaeologists on making art. It explores the relationship between archaeology and art practice, the interactions between materials and practitioners, and the processes that result in the objects and images we call 'art'.